PARTICULARITIES OF THE DENTIST - DENTAL TECHNICIAN COMMUNICATION IN THE DESIGN AND MANUFACTURE OF FIXED PARTIAL PROSTHESES - Steliana-Gabriela Buștiuc; Aureliana Caraiane; Elena-Claudia Sin; Rodica-Maria Murineanu; Gheorghe Raftu (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study The aim of this study was to evaluate the quality of communication between dentists and dental technicians regarding the transmission of data on the design and manufacture of fixed partial prostheses. Material and methods The studied group consists of 75 dental technicians, aged 25-60 years, who work in the private dental technology laboratories on the area of Constanța county. They were given a questionnaire with the items formulated in relation to the quality of the communication between the dentists and the dental technicians Results Most of the dental technicians do not receive information from the dentist about the age, gender, shape of the patient's face or photos of the patient's dentition. Regarding the design of the prosthesis, the dental technician discusses these aspects only sometimes with the dentist, and the information he receives on the order form is, in most cases, insufficient, the dental practitioners leaving the technician to decide on certain characteristics, such as: the design of the pontic elements, occlusal features, etc. Conclusions. Regarding the design of the prosthesis, the dental technician discusses these aspects only sometimes with the dentist, and the information he receives on the order form is, in most cases, insufficient, the dental practitioners leaving the technician to decide on certain characteristics, such as: the design of the pontic elements, occlusal features, etc